The Use and Effects of Smartphones in Higher Education - Alfawareh, Hejab Maazer; Jusoh, Shaidah (International Journal of Interactive Mobile Technologies (iJIM), 2017)
The purpose of this study is to investigate the use and effects of smartphones on academic staffs at a university level, especially in the Kingdom of Saudi Arabia. We conducted a survey study using questionnaires. The questionnaires were randomly distributed to 66 academic staffs who own a smartphone at the Northern Border University. This study discovers the smartphone had replaced a computer, and an email application was mostly used. The academic staffs also had utilized smartphone as a means for knowledge sharing. Social media applications were greatly used in teaching and learning. Despite the benefits of smartphone use, academic staffs had been negatively affected. This study also reveals that having a smartphone diverted academic staffs’ focus at work, created "check habits", and an artificial relationship; more than 90% of the respondents admitted that they put their smartphone besides their bed before sleep, and 61.41% of them claimed that they had the feelings of incompleteness whenever smartphones were not with them.